UPAYA PENCEGAHAN KEKERASAN TERHADAP ANAK DALAM PRESPEKTIF HUKUM PIDANA DAN KRIMINOLOGI DI KOTA TANJUNGPINANG - Widiyani, Heni; Ferilanda, Jelly Yanti; Arida, Maina; Eryanti, Niken Febri; Kamalia, Disya Putri (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
Violence against children is currently becoming a hot phenomenon, so violence against children has an impact on various places such as families, schools, playgrounds, Islamic boarding schools, and orphanages. This study focuses on violence against children in Tanjungpinang City, This study formulates the reasons for the phenomenon of violence against children in Tanjungpinang City using qualitative and juridical normative methods. The researchers' data collection technique uses interview techniques. Based on the results of the study, the author found that the causes of violence in Tanjungpinang City children are economic factors, stress or experiencing pressure, and the effects of pornographic films that create and maintain violence against children. In the problem, it is seen in the perspective of criminology in efforts to prevent children in Tanjungpinang City based on the sociological research approach of law raised in law. The results of the study explained that in 2021 there were 76 children as victims, in 2022 there were 83 children as victims, and in 2023 there were 90 children as victims. So that in total from 2021 to 2023 there were 249 cases of violence against children recorded in UPTD PPA Tanjungpinang City and Simfoni PPA. Forms of violence against children in Tanjungpinang City range from physical, psychological, neglect, sexual, and trafficking. It was recorded in the UPTD PPA Tanjungpinang City and the PPA Symphony, that the form of sexual violence was the most common form of violence from 2021 to 2023 in Tanjungpinang City. The fewest forms of violence from 2021 to 2023 were trafficking. Then the number of violence against children by age, the most are at the age of 13-18 years. Meanwhile, the highest number of violence against children based on education level was recorded in elementary schools from 2021 to 2022.